Weight Distribution of Minimal Cyclic Codes over a Finite Field - Singh, Inderjit; Rani, Seema (International Journal of Computer Sciences and Engineering, 2023)
Let Fq be the finite field with q elements, p, q be two odd primes with gcd(2p, q) = 1, multiplicative order of q modulo 2p^m is p^d (0?d?m-1), m ? 1 be an integer. In this paper, we obtain weight distribution of all the minimal(irreducible) cyclic codes of length 2pm over Fq by using their generating polynomials.